Transmittance spectra data of Cu₂Zn₁₋ₓMgₓSnS₄ nanoparticle solutions - Boiko Bohdan; Yermakov Maksym; Vasyliev Vitalii; Pshenychnyi Roman; Diachenko Oleksii (DataverseUA, 2025)
Transmittance spectra data of Cu₂Zn₁₋ₓMgₓSnS₄ nanoparticle solutions at x = 0.0, 0.1, 0.2, 0.3, 0.4, 0.5, and 0.6 in the wavelength range of 200-900 nm.